Parenteral methotrexate for patients with Crohn's disease: how to develop a high-quality and safe self-administration service. Issue 1 (16th November 2011) - Coltart, Iona; Blackmore, Laura; Caisley, Jane; Harris, Adam
Abstract : Parenteral methotrexate is recommended for patients with Crohn's disease who have failed treatment with thiopurines. There is no good evidence for the use of oral methotrexate, yet patients frequently receive this due to the difficulties associated with prescribing and administering an unlicensed, cytotoxic drug. We present our experience of developing a local service to provide our patients with the option to self-administer parenteral methotrexate in a safe and structured manner at home.